H(D) → D(H) + Cu(111) collision system: Molecular dynamics study of surface temperature effects - Vurdu, Can D; Güvenç, Ziya B (AIP Publishing, 2011)
All the channels of the reaction dynamics of gas-phase H (or D) atoms with D (or H) atoms adsorbed onto a Cu(111) surface have been studied by quasiclassical constant energy molecular dynamics simulations. The surface is flexible and is prepared at different temperature values, such as 30 K, 94 K, and 160 K. The adsorbates were distributed randomly on the surface to create 0.18 ML, 0.28 ML, and 0.50 ML of coverages. The multi-layer slab is mimicked by a many-body embedded-atom potential energy function. The slab atoms can move according to the exerted external forces. Treating the slab atoms non-rigid has an important effect on the dynamics of the projectile atom and adsorbates. Significant energy transfer from the projectile atom to the surface lattice atoms takes place especially during the first impact that modifies significantly the details of the dynamics of the collisions. Effects of the different temperatures of the slab are investigated in this study. Interaction between the surface atoms and the adsorbates is modeled by a modified London–Eyring–Polanyi–Sato (LEPS) function. The LEPS parameters are determined by using the total energy values which were calculated by a density functional theory and a generalized gradient approximation for an exchange-correlation energy for many different orientations, and locations of one- and two-hydrogen atoms on the Cu(111) surface. The rms value of the fitting procedure is about 0.16 eV. Many different channels of the processes on the surface have been examined, such as inelastic reflection of the incident hydrogen, subsurface penetration of the incident projectile and adsorbates, sticking of the incident atom on the surface. In addition, hot-atom and Eley-Rideal direct processes are investigated. The hot-atom process is found to be more significant than the Eley-Rideal process. Furthermore, the rate of subsurface penetration is larger than the sticking rate on the surface. In addition, these results are compared and analyzed as a function of the surface temperatures.
Keywords: 7. Clean energy